Pemikiran Imam al-Ghazali Tentang Hukum Islam - Zakiyatus Soimah (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2021)
The study aims to find out the extent of Imam al-Ghazali's legal thinking. Using qualitative approaches and literature studies, the study resulted in the conclusion that Imam al-Ghazali's method of legal excavation consisted of semantic, contextual, and textual approaches. The contextual approach of delving into the problem of iqtida, isharoh, lafad, understanding the law of its illat, understanding the meaning behind the spoken word and mafhum. A textual approach that addresses qiyas. The concept of ijtihad Imam al-Ghazali provides opportunities for Muslims who have the ability to arrive at the mujtahid position to preach. The concept of mujtahid not only stops at absolute mujtahid, but also includes mujtahid muqayyad which requires only some capacity on certain things